Keberagaman Tren Pendidikan Anti-Korupsi: Tinjauan Sistematis atas Praktik dan Tantangan Global - Yasmiati, Ni Luh Wayan; Sudatha, I Gde Wawan; Suartama, I Kadek; Santosa, Made Hery (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the development, effectiveness, challenges, and research gaps in the implementation of anti-corruption education globally during the 2015–2025 period. Employing a Systematic Literature Review (SLR) guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, the study systematically identified, evaluated, and synthesized 37 peer-reviewed articles indexed in the Scopus database. The findings indicate a significant increase in both academic publications and the implementation of anti-corruption education programs worldwide. These programs adopt diverse approaches, including curriculum integration, the use of digital media, and participatory learning strategies. Evidence of program effectiveness is reflected in behavioral changes and long-term social impacts reported in several studies. However, the review also reveals persistent challenges: cultural (social norms tolerant of corruption), structural (absence of national standards or policy frameworks), and technical (limited access to technological infrastructure). Furthermore, the research landscape shows notable gaps, such as the lack of longitudinal studies, minimal focus on vulnerable groups (e.g., children with disabilities), and underutilization of emerging tools like artificial intelligence (AI) and big data analytics. Future research is recommended to adopt interdisciplinary perspectives, develop context-based learning modules, and leverage advanced technologies to enhance engagement and scalability. Overall, the findings highlight the urgency of implementing holistic and adaptive strategies to strengthen the role of education in combating corruption at various levels of society.